2021
DOI: 10.3390/healthcare9060741
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Feeding Problems in Young Children with Gastrointestinal Diseases

Abstract: Feeding problems are associated with the consumption of a limited amount or restricted variety of foods and often occur in children with gastrointestinal diseases. The majority of studies to date do not use valid and reliable measurements to detect feeding problems. The aim of this cross-sectional study was to assess behavioral and skill-based feeding problems in young children with gastrointestinal diseases by using a well-established parent-reported feeding measure and identify demographic, anthropometric, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 71 publications
1
9
0
Order By: Relevance
“…In addition to changes in caregiver HRQoL, we observed a high prevalence of comorbidities among children undergoing gastrostomy tube placement. These findings are consistent with those reported in studies of children with feeding difficulties [ 16 , 17 ] and those reported in studies of children requiring gastrostomy tube placement [ 13 , 18 ]. Prior reports suggest that these comorbidities increase caregiver burden, which may decrease caregiver quality of life [ 4 , 13 ].…”
Section: Discussionsupporting
confidence: 92%
“…In addition to changes in caregiver HRQoL, we observed a high prevalence of comorbidities among children undergoing gastrostomy tube placement. These findings are consistent with those reported in studies of children with feeding difficulties [ 16 , 17 ] and those reported in studies of children requiring gastrostomy tube placement [ 13 , 18 ]. Prior reports suggest that these comorbidities increase caregiver burden, which may decrease caregiver quality of life [ 4 , 13 ].…”
Section: Discussionsupporting
confidence: 92%
“…Our study also focused on the early stage of self-feeding which is finger feeding. There is evidence to support that failure to develop self-feeding skills is associated with feeding difficulties (1,32). Finger feeding initiation between 6 and 9 months was negatively associated with BPFAS scores in healthy children in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Three patterns of ARFID restrictive eating have consistently been described, in both community and clinical samples: selective/neophobic (i.e., “picky” eating), poor appetite or limited interest in food, and fear of aversive consequences from eating [ 5 , 6 , 7 ]. Although largescale population prevalence estimates are not available, ARFID has been shown to be common in both community and clinical pediatric samples [ 5 , 8 , 9 ]. The short history of research on ARFID provides important descriptive data, but it is still insufficient for understanding its specifics and planning effective forms of treatment to patients and their families.…”
Section: Introductionmentioning
confidence: 99%
“…Common comorbidities of ARFID include neurodevelopmental disorders (e.g., autism), sensory integration disorders, alexithymia, intellectual disability, difficult temperament, high levels of externalization and internalization, psychomotor hyperactivity, anxiety disorders, obsessive-compulsive disorders, depressive disorders, suicide attempts and self-harm [ 13 , 15 , 18 , 19 , 20 , 21 , 22 ]. It is also not uncommon for ARFID to develop from childhood health problems that lead to gastrointestinal disturbances [ 9 , 23 , 24 , 25 ]. In such a case, the disorder results most often from the fear of negative somatic consequences of food intake (e.g., pain) and may be maintained by inadvertent negative reinforcement of disruptive mealtime behaviors by caregivers [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%